Polymer Latex for Use in Construction Applications

JP7652779B2Active Publication Date: 2025-03-27シントマードイチェラントゲゼルシャフトミットベシュレンクテルハフツング
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022535049
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-10
Filing Date
2020-12-07
Publication Date
2025-03-27
Estimated Expiration
2040-12-07

Smart Images

  • Figure 0007652779000001
    Figure 0007652779000001
  • Figure 0007652779000002
    Figure 0007652779000002
Patent Text Reader

Abstract

The present invention relates to a polymer latex obtained by aqueous emulsion polymerization of a mixture of ethylenically unsaturated monomers, and a building material, preferably a cementitious composition, containing the same: (a) a vinyl aromatic compound, (b) a conjugated diene, (c) a hydroxyalkyl ester of an ethylenically unsaturated acid in an amount of 2 to 10 wt %, based on the total weight of the monomers, and (d) an ethylenically unsaturated carboxylic acid or its salt in an amount of 0 to 0.15 wt %, based on the total weight of the monomers, wherein the weight ratio of the vinyl aromatic compound to the conjugated diene is at least 1.3:1, and the polymer latex contains a nonionic surfactant having an HLB of 17 to 19 in an amount of 2 to 10 wt %, based on the total weight of the monomers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polymer latices for use in construction applications, particularly, but not exclusively, suitable for cementitious compositions, and further to building materials, particularly cementitious compositions, comprising such polymer latices. [Background technology]

[0002] No. 4,368,077 relates to a styrene butadiene-based latex and its use in cementitious compositions. The SBR latex is prepared by emulsion polymerization in the presence of N-methylol methacrylamide and an anionic surfactant at a weight ratio of styrene to butadiene greater than 1.5.

[0003] WO 2003 / 27039 relates to an SBR latex usable in gypsum bonded wallboard. The SBR latex disclosed therein is preferably functionalized with 2-acrylamido-2-methylpropanesulfonic acid or a salt thereof. In a preferred embodiment, the latex is polymerized from a monomer composition comprising 2-6 wt. % 2-acrylamido-2-methylpropanesulfonic acid, 65-80 wt. % styrene, 15-13 wt. % butadiene, 0-3 wt. % hydroxyethyl acrylate, 0-10 wt. % acrylonitrile. Polymerization in the presence of an anionic surfactant is disclosed. A non-ionic surfactant may additionally be present. However, there is no disclosure regarding the amount of non-ionic surfactant.

[0004] EP1024154 discloses styrene butadiene rubber for use in cementitious compositions. The weight ratio of styrene to butadiene is greater than 1.5, and acrylamidomethylpropanesulfonic acid is present in the seed for polymerization of the latex. In the examples, an anionic surfactant is used, and hydroxyethyl acrylate can be present in an amount of 1.5 weight percent.

[0005] WO 2014 / 122031 relates to SBR latexes that can be used in cementitious compositions and that aim to replace butadiene with esters of unsaturated carboxylic acids to reduce costs. This reference discloses core-shell latex particles in which the core comprises vinyl aromatic compounds and esters of unsaturated carboxylic acids. Ethylenically unsaturated acids and other functional monomers may be present, inter alia, as hydroxyalkyl acrylates. The shell comprises vinyl aromatic monomers and conjugated dienes, as well as up to 10% by weight of additional monomers, such as hydroxyalkyl acrylates. The general description is silent regarding surfactants and their amounts. In the examples, a monomer composition that does not contain hydroxyalkyl acrylates is used, and the amount of nonionic surfactant is 0.33% by weight based on the total weight of monomers.

[0006] None of the cited documents address the improved properties of the cementitious composition imparted by the addition of a polymer latex, such as spreading, set retardation and strength enhancement of the cementitious composition.According to one aspect of the present invention, it is therefore an object of the present invention to provide a polymer latex that imparts an improved balance of properties such as spreading, set retardation and strength enhancement to the cementitious composition containing the polymer latex. Summary of the Invention

[0007] According to one aspect of the present invention, this object has surprisingly been achieved by a polymer latex obtained by aqueous emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: (a) vinyl aromatic compounds, (b) conjugated dienes, (c) a hydroxyalkyl ester of an ethylenically unsaturated acid in an amount of 2 to 10 weight percent, based on the total weight of monomers; and (d) an ethylenically unsaturated carboxylic acid or a salt thereof in an amount of 0 to 0.15% by weight, based on the total weight of the monomers; wherein the weight ratio of vinyl aromatic compound to conjugated diene is at least 1.3:1, and the polymer latex contains a nonionic surfactant having an HLB of 17-19 in an amount of 2-10% by weight, based on the total weight of monomers.

[0008] According to other aspects, the present invention relates to the use of said polymer latex in a cementitious composition and to a cementitious composition containing said polymer latex. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Monomer mixture: The polymer latex of the present invention is obtained by aqueous emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising the following components: (a) vinyl aromatic compounds, (b) conjugated dienes, (c) a hydroxyalkyl ester of an ethylenically unsaturated acid in an amount of 2 to 10 weight percent, based on the total weight of monomers; and (d) an ethylenically unsaturated carboxylic acid in an amount of 0 to 0.15 weight percent, based on the total weight of the monomers; Here, the weight ratio of vinyl aromatic compound to conjugated diene is at least 1.3:1.

[0010] Representative examples of vinyl aromatic monomers include, for example, styrene, α-methylstyrene, vinyltoluene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-t-butylstyrene, 5-t-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, vinylnaphthalene, vinyltoluene, vinylxylene, 2-vinylpyridine, 4-vinylpyridine, as well as 1,1-diphenylethylene and substituted 1,1-diphenylethylene, 1,2-diphenylethene and substituted 1,2-diphenylethylene. Mixtures of one or more vinyl aromatic compounds can also be used. Preferred monomers are styrene and α-methylstyrene, most preferably styrene. The vinyl aromatic compound can be used in the range of 24-70% by weight, preferably 38-65% by weight, more preferably 40-60% by weight, based on the total weight of the ethylenically unsaturated monomers. Thus, the vinyl aromatic compound can be present in an amount of 70% by weight or less, 68% by weight or less, 65% by weight or less, 63% by weight or less, 60% by weight or less, 58% by weight or less, based on the total weight of the ethylenically unsaturated monomers. The vinyl aromatic compound can be present in an amount of at least 24% by weight, at least 30% by weight, at least 33% by weight, at least 35% by weight, at least 38% by weight, at least 40% by weight, based on the total weight of the ethylenically unsaturated monomers. One skilled in the art will understand that any range defined by any of the lower and upper limits disclosed above is disclosed herein.

[0011] Conjugated diene monomers suitable for the present invention include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, 1,3-octadiene, 2-methyl-1,3-pentadiene, 2,3-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-hexadiene, 2,3-diethyl-1,3-butadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, 3,7-dimethyl-1,3,6-octatriene, 2-methyl-6-methylene-1,7-octadiene, 7-methyl-3-methylene The conjugated diene monomers include those selected from 1,6-octadiene, 1,3,7-octatriene, 2-ethyl-1,3-butadiene, 2-amyl-1,3-butadiene, 3,7-dimethyl-1,3,7-octatriene, 3,7-dimethyl-1,3,6-octatriene, 3,7,11-trimethyl-1,3,6,10-dodecatetraene, 7,11-dimethyl-3-methylene-1,6,10-dodecatriene, 2,6-dimethyl-2,4,6-octatriene, 2-phenyl-1,3-butadiene, 2-methyl-3-isopropyl-1,3-butadiene, 1,3-cyclohexadiene, myrcene, ocimene, and farnesene. 1,3-butadiene, isoprene, and combinations thereof are the preferred conjugated dienes. 1,3-butadiene is the most preferred diene. Typically, the amount of conjugated diene monomer may range from 15 to 45 weight percent, preferably 20 to 40 weight percent, more preferably 24 to 39 weight percent, based on the total weight of monomers. Thus, the conjugated diene may be present in an amount of at least 15 weight percent, at least 20 weight percent, at least 22 weight percent, at least 24 weight percent, based on the total weight of ethylenically unsaturated monomers.

[0012] Thus, conjugated diene monomers can be used in amounts up to 45%, up to 43%, up to 40%, up to 39%, up to 38% by weight based on the total weight of ethylenically unsaturated monomers. One of ordinary skill in the art will understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein.

[0013] The weight ratio of vinyl aromatic compound to conjugated diene in the monomer mixture is at least 1.3:1, preferably at least 1.5:1, more preferably at least 1.6:1, even more preferably at least 1.8:1, even more preferably at least 1.9:1, and most preferably at least 2.0:1.

[0014] Hydroxyalkyl esters of ethylenically unsaturated acids that can be used to prepare the polymer latex according to the invention include hydroxyalkyl acrylate and hydroxyalkyl methacrylate monomers based on ethylene oxide, propylene oxide and higher alkylene oxides or mixtures thereof. For example, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxybutyl acrylate. Preferably, the hydroxyalkyl (meth)acrylate monomer is 2-hydroxyethyl (meth)acrylate or 2-hydroxypropyl (meth)acrylate. The hydroxyalkyl (meth)acrylate monomer is present in an amount of 2-10% by weight, preferably 2-9% by weight, more preferably 2-7% by weight, and most preferably 2-6% by weight, based on the total weight of the ethylenically unsaturated monomers.

[0015] The monomer mixture according to the present invention comprises no more than 0.15% by weight, preferably no more than 0.1% by weight, more preferably no more than 0.05% by weight, even more preferably no more than 0.01% by weight of an ethylenically unsaturated carboxylic acid or its salt. Most preferably, the monomer mixture is free of ethylenically unsaturated carboxylic acids and their salts.

[0016] When present, the ethylenically unsaturated carboxylic acid or its salt can be selected from monocarboxylic and dicarboxylic acid monomers and their anhydrides and polycarboxylic acid partial esters. Examples of monocarboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, and examples of dicarboxylic acid monomers include fumaric acid, itaconic acid, maleic acid, cis-cyclohexene-1,2-dicarboxylic acid, dimethyl maleic acid, bromo maleic acid, 2,3-dichloro maleic acid, and (2-dodecen-1-yl) succinic acid. Examples of polycarboxylic acid partial esters include monomethyl maleate, monomethyl fumarate, monoethyl maleate, monoethyl fumarate, monopropyl maleate, monopropyl fumarate, monobutyl maleate, monobutyl fumarate, mono(2-ethylhexyl) maleate, mono(2-ethylhexyl) fumarate. Examples of other ethylenically unsaturated carboxylic acids include vinyl acetate, vinyl lactate, and their salts.

[0017] The monomer mixture according to the present invention may, if necessary, further comprise (e) an ethylenically unsaturated monomer which is copolymerizable with and different from the monomers (a) to (d).

[0018] The ethylenically unsaturated monomer (e) may be selected from the following components: (e1) an ethylenically unsaturated sulfonic acid, preferably present in the monomer mixture in an amount of 0 to 10% by weight, preferably 0 to 6% by weight, more preferably 0 to 4% by weight, even more preferably 0 to 2% by weight, even more preferably 0 to 1% by weight, based on the total weight of the ethylenically unsaturated monomers; (e2) C of acrylic acid or methacrylic acid 1 ~C 20 Alkyl esters, preferably in an amount of 0 to 25% by weight, preferably 0 to 10% by weight, based on the total weight of the ethylenically unsaturated monomers; (e3) An ethylenically unsaturated nitrile compound, preferably in an amount of 0 to 15% by weight, preferably 0 to 10% by weight, based on the total weight of the ethylenically unsaturated monomers.

[0019] The ethylenically unsaturated sulfonic acid (e1) is preferably selected from styrenesulfonic acid, vinylsulfonic acid, allylsulfonic acid, methallylsulfonic acid, (meth)acrylic acid-3-sulfopropyl ester and 2-acrylamido-2-methylpropanesulfonic acid. Most preferably, the monomer mixture according to the invention is free of ethylenically unsaturated sulfonic acids.

[0020] Alkyl esters (e2) of ethylenically unsaturated acids which can be used according to the invention include n-, iso- or tert-alkyl esters of acrylic or (meth)acrylic acid, in which the alkyl group has 1 to 20 carbon atoms.

[0021] Generally, preferred alkyl esters of (meth)acrylic acid are 1 -C 10 Alkyl (meth)acrylate, preferably C 1 -C 8 Can be selected from alkyl (meth)acrylate. Examples of such acrylate monomers include n-butyl acrylate, secondary butyl acrylate, ethyl acrylate, hexyl acrylate, tert-butyl acrylate, 2-ethyl-hexyl acrylate, isooctyl acrylate, 4-methyl-2-pentyl acrylate, 2-methylbutyl acrylate, methyl methacrylate, butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate and cetyl methacrylate. Methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate and combinations thereof are preferred.

[0022] Typically, the alkyl (meth)acrylate monomers can be present in an amount of 25% by weight or less, 23% by weight or less, 20% by weight or less, 18% by weight or less, 16% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less, based on the total weight of the ethylenically unsaturated monomers.

[0023] Unsaturated nitrile monomers (e3) that can be used according to the invention include polymerizable unsaturated aliphatic nitrile monomers containing 2 to 4 carbon atoms in a linear or branched arrangement, which may be substituted with either acetyl or additional nitrile groups. Such nitrile monomers include acrylonitrile, methacrylonitrile, α-cyanoethyl acrylonitrile, fumaronitrile and combinations thereof, with acrylonitrile being most preferred. These nitrile monomers may be included in amounts of 15% by weight or less, 14% by weight or less, 12% by weight or less, 10% by weight or less, 8% by weight or less, 6% by weight or less, 4% by weight or less, 2% by weight or less, or 1% by weight or less, based on the total weight of the ethylenically unsaturated monomers.

[0024] According to the present invention, it is preferred that the polymer latex does not contain core / shell particles.

[0025] Method for preparing the polymer latex of the present invention: The latex polymer (I) according to the present invention can be prepared by any emulsion polymerization process known to those skilled in the art, provided that the monomer mixtures defined herein are used.The process described in EP-A-792891 is particularly suitable.

[0026] In the emulsion polymerization for preparing the polymer latex of the present invention, a seed latex may be employed. The seed latex is preferably prepared separately, and the emulsion polymerization is carried out in the presence of the separately prepared seed latex. The seed latex particles are preferably present in an amount of 0.01 to 10, preferably 1 to 5 parts by weight, based on 100 parts by weight of the total ethylenically unsaturated monomers used in the polymer latex, including those for making the seed particles, such as the oxirane-functional latex particles (b). Thus, the lower limit of the amount of seed latex particles can be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5 parts by weight. The upper limit of the above amount can be 10, 9, 8, 7, 6, 5.5, 5, 4.5, 4, 3.8, 3.6, 3.4, 3.3, 3.2, 3.1 or 3 parts by weight. One of ordinary skill in the art will recognize that any range formed by any of the explicitly disclosed lower and upper limits is expressly encompassed herein.

[0027] The above-mentioned process for the preparation of latex polymer (I) can be carried out in the absence or presence of one or more emulsifiers, in the absence or presence of one or more colloids, and in the presence of one or more initiators at temperatures between 0 and 130° C., preferably between 0 and 100° C., particularly preferably between 10 and 95° C., very particularly preferably between 20 and 90° C., including all values ​​and subvalues ​​therebetween, in particular 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120 and 125° C.

[0028] The initiator that can be used in carrying out the present invention includes water-soluble and / or oil-soluble initiators that are effective for polymerization purposes.Representative initiators are well known in the art, and include, for example, azo compounds (e.g., AIBN, AMBN, and cyanovaleric acid), inorganic peroxy compounds (e.g., hydrogen peroxide, sodium, potassium, and ammonium peroxydisulfates, peroxycarbonates, and peroxyborates), organic peroxy compounds (e.g., alkyl hydroperoxides, dialkyl peroxides, acyl hydroperoxides, and diacyl peroxides), and esters (e.g., tertiary butyl perbenzoate), as well as combinations of inorganic and organic initiators.

[0029] The initiator is used in an amount sufficient to initiate the polymerization reaction at the desired rate. In general, an amount of initiator of 0.01 to 5 weight percent, preferably 0.1 to 4 weight percent, based on the weight of the total polymer, is sufficient. Most preferably, the amount of initiator is 0.01 to 2 weight percent, based on the total weight of the polymer. The amount of initiator includes all values ​​and subvalues ​​therebetween, particularly 0.01, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 4, and 4.5 weight percent, based on the total weight of the polymer.

[0030] The above inorganic and organic peroxy compounds may also be used alone or in combination with one or more suitable reducing agents, as is well known in the art. Examples of such reducing agents that may be mentioned are sulfur dioxide, alkali metal disulfites, alkali metal and ammonium hydrogen sulfites, thiosulfates, dithionite and formaldehyde sulfoxylates, hydroxylamine hydrochloride, hydrazine sulfate, iron(II) sulfate, copper naphthenate, glucose, sulfonic acid compounds such as sodium methanesulfonate, and amine compounds such as dimethylaniline and ascorbic acid. The use of proprietary sodium salts of organic sulfinic acid derivatives, such as Bruggolite® FF6 or Bruggolite® FF6M, is more preferred. The amount of reducing agent is preferably between 0.03 and 10 parts by weight per part by weight of polymerization initiator.

[0031] Suitable surfactants or emulsifiers for stabilizing latex particles include conventional surfactants for polymerization processes. Surfactants can be added to the aqueous phase and / or the monomer phase. In a seeded process, an effective amount of surfactant is an amount selected to support colloidal stabilization of the particles, minimizing interparticle contact and preventing agglomeration. In a non-seeded process, an effective amount of surfactant is an amount selected to affect particle size.

[0032] Since the polymer latex of the present invention contains 2-10% by weight of a nonionic surfactant having an HLB of 17-19 based on the total weight of the ethylenically unsaturated monomers, such an amount of nonionic surfactant can be used in the emulsion polymerization process. Of course, it is also possible to use none or only a part of the total amount of nonionic surfactant required in the emulsion polymerization process, and add the remaining amount to the final polymer latex after the emulsion polymerization process is completed. It is preferable to add the nonionic surfactant after the reaction.

[0033] Suitable nonionic surfactants having an HLB of 17-19 can be selected from alkyl ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethylene glycol-propylene glycol block copolymers, or tristyrylphenol ethoxylates. Preferred nonionic surfactants have an HLB value of 17-18.5, more preferably 17-18. The HLB value is calculated as the quotient of the molar mass of the hydrophilic portion of the surfactant and the total molar mass of the surfactant multiplied by 20. The nonionic surfactant is present in the polymer latex of the present invention in an amount of 2-10% by weight, preferably 2-8% by weight, more preferably 2-7% by weight, based on the total weight of ethylenically unsaturated monomers.

[0034] Thus, the amount of nonionic surfactant in the polymer latex of the present invention can be at least 2% by weight, or at least 2.5% by weight, at least 3% by weight, at least 3.5% by weight, at least 4% by weight, at least 4.5% by weight, or at least 5% by weight, based on the total weight of ethylenically unsaturated monomers. The amount of nonionic surfactant in the polymer latex of the present invention can be up to 10% by weight, or up to 9.5% by weight, up to 9% by weight, up to 8.5% by weight, up to 8% by weight, up to 7.5% by weight, up to 7% by weight, up to 6.5% by weight, up to 6% by weight, based on the total weight of ethylenically unsaturated monomers. Those skilled in the art will understand that all ranges formed by any of the above stated limits are disclosed herein.

[0035] Optionally, anionic surfactants can be used in addition to nonionic surfactants.Representative anionic surfactants include saturated and ethylenically unsaturated sulfonic acids or their salts, such as unsaturated hydrocarbon sulfonic acids (such as vinyl sulfonic acid, allyl sulfonic acid and methallyl sulfonic acid) and their salts; aromatic hydrocarbon acids (such as p-styrene sulfonic acid, isopropenyl benzene sulfonic acid and vinyloxy benzene sulfonic acid) and their salts; sulfoalkyl esters of acrylic acid and methacrylic acid (such as sulfoethyl methacrylate and sulfopropyl methacrylate) and their salts, and 2-acrylamido-2-methylpropane sulfonic acid and their salts; alkylated diphenyl oxide disulfonates, sodium dodecyl benzene sulfonate, dihexyl ester of sodium sulfosuccinate, sodium alkyl esters of sulfonic acid, ethoxylated alkylphenols and ethoxylated alcohols; fatty alcohol (poly)ether sulfates.The presence of anionic surfactants during polymerization process can be advantageous to aid process stability and latex stability.

[0036] Instead of or in addition to the above surfactants, various protective colloids can also be used. Suitable colloids include polyhydroxy compounds such as partially acetylated polyvinyl alcohol, casein, hydroxyethyl starch, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polysaccharides and decomposed polysaccharides, polyethylene glycols and gum arabic. Preferred protective colloids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose. Generally, these protective colloids are used in a content of 0 to 10, preferably 0 to 5, more preferably 0 to 2 parts by weight, based on the total weight of the monomers. The amount of protective colloid includes all values ​​and subvalues ​​therebetween, in particular 1, 2, 3, 4, 5, 6, 7, 8 and 9% by weight, based on the total weight of the monomers.

[0037] It is often recommended that the emulsion polymerization is further carried out in the presence of buffer substances and chelating agents. Suitable substances are, for example, alkali metal carbonates and hydrogen carbonates, alkali metal phosphates and pyrophosphates (buffer substances) and alkali metal salts of ethylenediaminetetraacetic acid (EDTA) or hydroxyl-2-ethylenediaminetriacetic acid (HEEDTA) as chelating agents. The amount of buffer substances and chelating agents is usually 0.001 to 1.0% by weight, based on the total amount of monomers.

[0038] In addition, it may be advantageous to use chain transfer agents (regulators) in the emulsion polymerization. Typical agents are, for example, thioesters, 2-mercaptoethanol, 3-mercaptopropionic acid, iso-octyl-3-mercaptopropionate, and C 1 -C 12 The chain transfer agent is an organic sulfur compound such as an alkyl mercaptan, preferably n-dodecyl mercaptan and t-dodecyl mercaptan. The amount of the chain transfer agent, if present, is usually 0.05 to 3.0% by weight, preferably 0.2 to 2.0% by weight, based on the total weight of the monomers used.

[0039] Polymer Latex: The polymer latex of the present invention is prepared by aqueous emulsion polymerization using the monomer mixture as described above. If not already used in sufficient amounts in the emulsion polymerization, non-ionic surfactants, including the preferred surfactants described above, can be added to the polymer latex obtained from the emulsion polymerization to provide the above-mentioned required amount of non-ionic surfactant, including the preferred amounts.

[0040] Various other additives and ingredients can be added to prepare the polymer latex of the present invention. Such additives include, for example, defoamers, wetting agents, thickeners, plasticizers, fillers, pigments, dispersants, optical brighteners, antioxidants, biocides and metal chelating agents. Known defoamers include silicone oils and acetylene glycols. Commonly known wetting agents include alkylphenol ethoxylates, alkali metal dialkyl sulfosuccinates, acetylene glycols and alkali metal alkyl sulfates. Typical thickeners include polyacrylates, polyacrylamides, xanthan gums, modified celluloses, micro- or nano-cellulose fibers, polyurethane-type associative thickeners, or particulate thickeners such as silica and clay. Typical plasticizers include mineral oil, liquid polybutenes, liquid polyacrylates, polyalkylene glycols such as polypropylene glycol or polybutylene glycol, carboxylic acid esters such as the alkyl esters of adipic acid, citric acid, phthalic acid, terephthalic acid, isophthalic acid or trimellitic acid, and lanolin. Titanium dioxide (TiO 2 ), calcium carbonate and clay are typically used fillers.

[0041] Building materials: The polymer latex of the present invention may be used in building materials, especially in applications where the curing behavior of the building material may be influenced by the polymer latex of the present invention.

[0042] The polymer latices of the present invention are particularly suitable for imparting an improved balance of properties to building materials, preferably cementitious compositions. The cementitious compositions according to the present invention may be selected from concrete, cement-based building materials (such as screeds, tile adhesives or cement-based interfacial agents), and mortars (such as bricklaying mortars, gypsum mortars, repair mortars, waterproofing mortars, self-leveling mortars, external insulation adhesive mortars, decorative mortars, insulation mortars, or flooring mortars).

[0043] The weight ratio of polymer to cement used in these cementitious compositions is between 0.02 and 0.4, generally between 0.05 and 0.2.

[0044] The cementitious compositions may contain conventional ingredients in conventional amounts that are present in each cementitious composition depending on the desired end use.

[0045] Typical compounds used in such cementitious systems other than water are ordinary Portland cement, special Portland cement, high alumina cement and blended cements, as well as fine and coarse aggregates such as river sand, gravel, crushed sand and stone, silica sand and fly ash. Pigments may be added to achieve the desired color. Natural or synthetic glass, carbon and metal fibers may be added to strengthen the cementitious system. Additives may be added to adjust processing or mechanical properties. Examples are plasticizers, superplasticizers, flow agents, set accelerators, set retarders, defoamers or air entrainers.

[0046] Another suitable use of the polymer latex of the present invention is as a filler material for brick, glass or metal.

[0047] The present invention will now be described in more detail with reference to the following examples. EXAMPLES

[0048] The polymer latex compositions used in the examples and comparative examples were prepared by free radical emulsion polymerization using a combination of initial charge and feed. Polystyrene seeds with an average particle size of 36 nm in an amount of 1.2 parts by weight based on the total monomer (hereinafter referred to as pphm) were used in the initial charge, together with water (30 pphm) and HEEDTA (0.05 pphm) as a complexing agent. After heating the initial charge to 85° C. under continuous stirring, the polymerization reaction was started by starting the feed of ammonium persulfate (1 pphm). The temperature was kept constant at 85° C. 10 minutes after starting the persulfate feed, the monomers, anionic surfactants (C at 0.5 pphm) according to Table 1 were added. 13 -C 15 Parts of alkylarylsulfonate, 0.8 parts of t-dodecyl mercaptan as a chain transfer agent, and water were added to the reactor at a constant feed rate over 6 hours. Then, post-activation with 0.25 pphm of ammonium persulfate to reduce residual monomer was started and continued for 3 hours. The product was cooled to ambient temperature, sieved on a filter cloth with a 50 μm mesh width, and the pH was adjusted to 7.5 with 10% aqueous sodium hydroxide solution. Next, a nonionic surfactant according to Table 1 was added and homogenized for 5 minutes. The total solids content of the final latex was adjusted to 50% by weight, and the final pH was adjusted to 8.5 with sodium hydroxide solution.

[0049] The particle size of the latex was measured by Mastersizer 2000 (Malvern) and was found to be 155 to 160 nm.

[0050] Polymer modified cement mortars were prepared using latex according to Table 1. For each mortar, 900 g of CEM I 32.5 Portland cement (Schwenk) was mixed with 1350 g of reference sand according to EN196. 0.6% antifoaming agent, Tego Antifoam 2-89 (Evonik), was added to the latex before use. Test mortars were prepared with water and latex and thoroughly mixed in a planetary mixer (Hobart N50) equipped with stirring blades at 140 rpm for 1 min followed by 280 rpm for 1 min to obtain a polymer-cement ratio of 0.075 (dry to dry) and a water-cement ratio of 0.38 (342 g water and 67.5 g polymer in total).

[0051] The mortars were used to measure the density according to DIN EN 196-1:2016-11, the slump behavior immediately after mixing, after 20 minutes, 40 minutes and 60 minutes according to DIN EN 1015-3:200-5, as well as the compressive and flexural strength after 48 hours, 7 days and 28 days according to DIN EN 196-1:2016-11.

[0052] Target: Mortar density >2g / mL. Immediately after slump test: >16cm, after 20 minutes: >14cm, after 40 minutes: >13cm, after 60 minutes: >12cm. Compressive strength after 48 hours: >4.5MPa, after 7 days: >6MPa, after 28 days: >8.5MPa. Flexural strength after 48 hours: >18MPa, after 7 days: >25MPa, after 28 days: >35MPa.

[0053] The results are shown in Table 2.

[0054] [Table 1]

[0055] [Table 2]

Claims

1. A polymer latex obtained by aqueous emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: (a) a vinyl aromatic compound, (b) conjugated dienes, (c) a hydroxyalkyl ester of an ethylenically unsaturated acid in an amount of 2 to 10 weight percent, based on the total weight of monomers; and (d) an ethylenically unsaturated carboxylic acid or its salt in an amount of 0 to 0.15 weight percent, based on the total weight of monomers; wherein the weight ratio of vinyl aromatic compound to conjugated diene is at least 1.3:1 and the polymer latex comprises a nonionic surfactant having an HLB of 17-19 in an amount of 2-10 wt %, based on the total weight of monomers.

2. 2. The polymer latex of claim 1, wherein the vinyl aromatic compound is selected from styrene, alpha-methylstyrene, 4-methylstyrene, alpha-chlorostyrene, 4-chlorostyrene, divinylbenzene, 4-methoxy-3-methylstyrene, 3,4-dimethyl-alpha-methylstyrene, and combinations thereof.

3. The polymer latex of claim 1 or 2, wherein the vinyl aromatic compound is present in the monomer mixture in an amount of from 24 to 70 weight percent, based on the total weight of the ethylenically unsaturated monomers.

4. The polymer latex according to any one of claims 1 to 3, wherein the conjugated diene is selected from 1,3-butadiene, 2-chloro-1,3-butadiene, isoprene, conjugated linear and branched pentadiene and hexadienes and combinations thereof.

5. The polymer latex of any one of claims 1 to 4, wherein the conjugated diene is present in the monomer mixture in an amount of from 16 to 45 weight percent, based on the total weight of the ethylenically unsaturated monomers.

6. The polymer latex according to any one of claims 1 to 5, wherein the hydroxyalkyl ester of an ethylenically unsaturated acid is selected from 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.

7. 7. The polymer latex of any one of claims 1 to 6, wherein the hydroxyalkyl ester of an ethylenically unsaturated acid is present in the monomer mixture in an amount of from 2 to 9 weight percent, based on the total weight of ethylenically unsaturated monomers.

8. The polymer latex of any one of claims 1 to 7, wherein the monomer mixture comprises 0.1% by weight or less of an ethylenically unsaturated carboxylic acid or salt thereof.

9. The polymer latex of any one of claims 1 to 8, wherein the monomer mixture further comprises (e) an ethylenically unsaturated monomer that is copolymerizable with and different from the monomers (a) to (d).

10. The polymer latex according to any one of claims 1 to 9, wherein the ethylenically unsaturated monomer (e) is selected from (e1) to (e3): (e1) ethylenically unsaturated sulfonic acids, (e2) C of acrylic acid or methacrylic acid 1 ~C 20 Alkyl esters, (e3) Ethylenically unsaturated nitrile compounds.

11. 11. The polymer latex according to any one of claims 1 to 10, wherein the non-ionic surfactant is selected from alkyl ethoxylates, alkylphenol ethoxylates, fatty acid ethoxylates, ethylene glycol-propylene glycol block copolymers or tristyrylphenol ethoxylates, and / or the non-ionic surfactant has an HLB value of 17 to 18.5, and / or the non-ionic surfactant is present in the polymer latex in an amount of 2 to 9 wt%, based on the total weight of ethylenically unsaturated monomers.

12. The polymer latex according to any one of claims 1 to 11, further comprising an anionic surfactant.

13. The polymer latex of any one of claims 1 to 12, wherein the polymer latex does not comprise core / shell particles.

14. A building material comprising the polymer latex according to any one of claims 1 to 13.

15. Use of the polymer latex according to any one of claims 1 to 13 in building materials.

Citation Information

Patent Citations

  • Cement composition

    JP1978134823A

  • Cementitious composition

    JP1990018346A

  • Concrete admixture

    JP2002234763A

  • Polymer dispersion, use of polymer dispersion and powder and granule produced from polymer dispersion, and method of improving mechanical strength, elasticity and processability of building material

    JP2003301015A

  • Water-based quick-drying composition and quick-drying coating composition

    JP2011195760A